Daya Tahan Tudung Akrosom dan Membran Plasma Spermatozoa Sapi Bali yang Dipaparkan pada Suhu Ruang - Trio Mohammad Syafi'i; Bayu Rosadi (Jurnal Produksi Ternak Terapan, 2022)
This study aimed to determine the effect of storage at room temperature on the durability of the acrosome cap and plasma membrane of Bali cattle spermatozoa. This research was conducted at the Reproduction Laboratory of the Faculty of Animal Husbandry, Jambi University. The experiment was carried out using a completely randomized design  with 4 treatments and 6 replications. Storage treatment at room temperature consisted of T0: no storage (control),T1: storage for 2 hours, T2: storage for 4 hours, T3: storage for 6 hours. The data obtained from each variable analyzed with variance. The treatment had a significant effect, so Duncan's further test was carried out. The process of calculating the data using the SPSS program. From the results of this study, it was found that storage of spermatozoa at room temperature reduced the quality of Bali cattle's spermatozoa against the acrosome hood, plasma membrane, and spermatozoa recovery rate (P<0.05). At storage for up to 4 hours, both 44,33% acrosomal cap and 52.83% recovery rate were still eligible for insemination. In plasma membrane storage at room temperature ranging from 0 hours 56.60% to 6 hours 35.83% showed a fairly low average, which was below 60% as the minimum requirement for insemination